FIDUCIARY GUARANTEES IN THE SUSTAINABLE FINANCE SYSTEM: BETWEEN CREDIT ACCESS AND CONSUMER PROTECTION - Endang Mulyadin, (Proceeding International Conference on Social Sciences, 2026)
This article examines fiduciary security within the context of Indonesia’s sustainable financial system, focusing on the imbalance between legal certainty for creditors and the protection of consumer rights. Fiduciary security serves as a legal instrument that protects creditors without restricting debtors from utilizing the secured object. Although Law Number 2 42 of 1999 concerning Fiduciary Security provides a strong legal foundation for both fiduciary grantors and recipients, the execution of fiduciary objects in practice frequently violates the principle of due process of law, particularly when execution is carried out without a court decision. This situation creates a legal imbalance between creditors and debtors and poses a risk of diminishing public trust in the financing system. This study highlights the importance of consumer protection in the implementation of fiduciary agreements and the need to update regulations to align with the principles of sustainable finance, which incorporate social and environmental dimensions (ESG). The Constitutional Court Decision Number 18/PUU-XVII/2019 affirms that fiduciary execution cannot be carried out unilaterally but must follow a lawful legal mechanism. Accordingly, this study proposes the reformulation of policies that not only strengthen debtor protection but also support the sustainability of the financial system, promote more inclusive access to financing, and integrate sustainability principles into fiduciary regulation. Using a statutory approach combined with normative qualitative analysis, this article aims to formulate legal recommendations that are fair, transparent, and grounded in economic sustainability by balancing market interests with social protection. Such reforms are essential to maintaining the credibility and fairness of Indonesia’s financial system in the face of global challenges that increasingly demand sustainability and social responsibility in every financing practice.